Was Bread Giffen? The Demand for Food in England Circa 1790 - Koenker, Roger (The Review of Economics and Statistics, 1977)
Two seminal budget studies by David Davies (1795) and Frederick Eden (1797) are employed below to investigate place of bread in diets of English rural laborers at end of eighteenth century.' Because of considerable geographic and temporal dispersion in prices of foodstuffs found in these budgets, they afford a unique opportunity to study influences of both prices and income on individual household consumption decisions. In particular a test is made of famous hypothesis, attributed by Marshall to Robert Giffen,2 that a rise in price of bread, ceteris paribus, increases its consumption among lower classes. Wheaten bread was, in Middle Ages, a luxury food of landed classes in Europe. Its gradual introduction into laboring class diets in modern period prompted David Landes (1969, p. 47) to conclude, ... one of best signs of comfort in Europe is consumption of white bread. The transition in England to wheat as the almost universal bread corn of whole people took place, according to Sir William Ashley (1928, pp. 1-2) primarily in eighteenth century and was virtually complete by 1795. The rise of wheat occurred most rapidly in southern and eastern counties and was favored by a more capitalistic agriculture since it often required special liming, other fertilization, and tilling. To contemporaries, and some modern historians, this change to wheaten bread seemed, for purely psychological reasons, to be irreversible. Radcliffe Salaman (1949, pp. 480-481) writes: